Substandard Language Phenomena in Artistic Discourse - Anzhelika V. Korolkova; Tatyana S. Novikova (RUDN Journal of Language Studies, Semiotics and Semantics)
It should be noted that in the fiction of the XX century, lexical units from various types of jargon, argot, youth slang are quite common, but the theme and communicative goal of the author of the text play an important role. The article examines the use of various substandard linguistic phenomena in the artistic discourse of the second half of the XX century - early XXI century. Since artistic discourse is a reality reinterpreted by the creative imagination of the author, then in the second half of the XX century, the use of substandard vocabulary and phraseology became necessary in a number of literary texts. Numerous linguistic studies note a certain feature: the activation of substandard vocabulary and its use in colloquial speech reduce the expressive potential of the vocabulary and phraseology of the standard, which correlates with the literary language. Analyzing substandard vocabulary within the framework of the artistic space of Russian literature of the late XX - early XXI century, it should be noted that this vocabulary has become actively in demand in works of various genres. In this context, we can note its active use in works of the detective genre, in fiction and fiction-publicistic works that comprehend the era of the Great Terror, as well as in works about youth and for youth young people. Modern research in the field of studying the substandard vocabulary of artistic discourse allows us to fully analyze the modern language space. The modern language substandard implements various functions in literary texts, from nominative to cognitive and cumulative, from the expression of emotions to vivid evaluativeness. The substandard is currently becoming a source of replenishment of the stylistically reduced layer of modern colloquial speech.